The Stylistics Elements of Figurative Language in Snow White and the Huntsman Movie and the Implications toward EFL Teaching - Karunia Eka Nafilatul Janah; Pratiwi Retnaningdyah; Ali Mustofa (Yayasan Visi Intan Permata, 2022)
Several previous studies have proven that the stylistics elements of figurative language were found in many literary works. Besides, it is essential for the students to develop literary competence, such as the ability to analyze the elements of figurative language. Hence, this research is aimed at investigating the stylistics elements of figurative language in a movie entitled Snow White and the Huntsman as well as the implications toward English as a foreign language (EFL) teaching. The stylistics elements of figurative language in this research focused on Epizeuxis, Parallelism, Prolepsis, Simile, and Chiasmus. This research applied qualitative design of research, while the data collecting technique is documentation as the movie is used to gather the data. Then, the data were analyzed using stylistics elements of figurative language theory, which are Epizeuxis, Simile, Prolepsis, Parallelism, and Chiasmus. The results revealed that there were 26 stylistics elements of figurative language in the movie consisting of 15 Epizeuxis, 5 Prolepsis, 4 Simile, and 2 Chiasmus. Furthermore, the results also found out that the stylistics elements of figurative language have some useful implications toward EFL teaching so that the teachers can implement some stylistics elements of figurative language in the classroom through some activities for teaching and learning. Finally, future researchers who want to conduct a research that is similar to this field of research are highly encouraged to analyze more stylistics elements of figurative language, so that the results of the research can reveal more various results